Integralização e marginalização: uma revisão bibliográfica sobre a questão da população em situação de rua em Campinas-SP - D’Abreu, Luiz Felipe Garcia Vilhete (Universidade Federal de São Carlos, 2024)
The present study focuses on the issue of the homeless population and the theoretical production on this topic in Brazil. As this is a highly debated theme in Brazilian society, the investigation aims to systematize and review the productions regarding the situation of homelessness in Campinas-SP. This serves as a means to aid the understanding of this social issue and guide future studies related to the topic. Despite a slight decrease in inequality in Brazil demonstrated by new budgetary and social policies, it has been observed that the situation of homelessness continues to worsen. This persists as a structural problem of inequality and distribution of resources and services. In December 2022, an academic scientific production survey was conducted in the areas of languages, collective health, social sciences, philosophy, education, geography and architecture, as well as those related to street life in the city of Campinas. The survey utilized the theses available in the CAPES theses and dissertations repository and Google Scholar. The search terms "Situação de Rua" (Homelessness) and "Campinas" yielded two articles and ten doctoral theses that addressed the theme. The literature review revealed that the most commonly used analytical tools involve qualitative research, employing participant observation through ethnographies, interviews, and life history accounts. The studies focused on the city center of Campinas as a specific area of inquiry. These works concluded that there are still many topics to be explored within the debates on homelessness in Campinas. These include issues related to race, studies on people with disabilities, LGBTQ+ individuals, immigration studies, sexuality and homelessness, experimental studies examining causes and effects linked to the experiences of the homeless, medium and long-term monitoring of life on the streets, and knowledge in the field of economics seeking to understand the direct impacts of the economy on homelessness within the municipal context. The studies also portray the relationships of people experiencing homelessness with the urban environments of the city, the subjective dimension of this population, and their integration and marginalization through social assistance institutions.
Integration and marginalization: a bibliographic review on the issue of the homeless population in Campinas, São Paulo.
Keywords: População em Situação de Rua; Campinas; Direitos humanos; Revisão bibliográfica; CIENCIAS HUMANAS::SOCIOLOGIA